Optimization of the structures at shakedon and Rosen`s optimality criterion = Optymalizacja konstrukcji w stanie przystosowania a kryterium optymalności Rosena - Alawdin, Piotr; Atkočiunas, Jouzas; Liepa, Liudas (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Paper focuses on the problems of application of extreme energy principles and nonlinear mathematical programing in the theory of structural shakedown. By means of energy principles, which describe the true stress-strain state conditions of the structure, the dual mathematical models of analysis problems are formed (static and kinematic formulations).
Keywords: przystosowanie; ekstremalne zasady energetyczne; projektowanie optymalne; programowanie matematyczne; kryterium optymalności Rosena; shakedown; extreme energy principles; optimal design; mathematical programming; Rosen`s optimality criterion